An Unrecognised Case of a Scapula Fracture Sustained through an Unusual Indirect Mechanism - Feiran Wu; Asim Rajpura; Mohammad Shahid; Dilraj Sandher (Case Reports in Orthopedics)
Scapula fractures following low-velocity injuries are extremely rare but can be a missed associated fracture of other upper limb injuries. We describe the case of a patient who sustained a fracture of the scapula through an unusual and hitherto unreported indirect mechanism. The injury was associated with a radial head fracture and initially missed on presentation. This case highlights the need for increased vigilance when diagnosing injuries with unusual mechanisms.